Plum-blossom needle plus Chinese herbal medicine for alopecia areata: A protocol for systematic review and meta analysis. Issue 41 (9th October 2020) - Tang, Genhua; Xiong, Jun; Fan, Qian; Guo, Han; Zhou, Xingchen; Zhu, Siyuan; Zhong, Zhiying; Chen, Jun; Lu, Lunbin
Abstract: Background: Alopecia areata (AA) is a common, inflammatory, nonscarring type of hair loss that is characterized by depression, anxiety and social isolation. In recent years, Plum-blossom needle plus Chinese herbal medicine has gradually shown its clinical advantages and been more and more widely used in China. Whereas, there has been no systematic review and meta-analysis. The purpose of this study is to estimate the safety and effectiveness of Plum-blossom needle plus Chinese herbal medicine in AA treatment. Methods: Seven databases as following: PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), Chinese Scientific Journal Database (VIP), and Chinese Biomedical Literatures Database (CBM) will be searched from their inception to August 2020. Two reviewers (LBL and ZYZ) will respectively regulate research selection, data extraction, and risk of bias assessment. A third reviewer will be settled to consulting, if necessary. Review Manager Software 5.4 will be implemented for this study. Results: The results will be published in a peer-reviewed medical journal. This meta-analysis will provide a synthetic review of the credible evidence for the treatment of Plum-blossom needle plus Chinese herbal medicine with AA. Conclusions: This systematic review and meta-analysis expects to provide high-quality evidence regarding the synergistic effect of Plum-blossom needle plus Chinese herbal medicine treatment for AA.